PENGARUH TRANSPARANSI PEMERINTAH DAERAH DAN KEPERCAYAAN PUBLIK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KABUPATEN GOWA - Hidayat, Julia; Arman, Andi; Rayyani, Wa Ode (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of local government transparency and public trust on individual taxpayer compliance in Gowa Regency. The research was conducted among individual taxpayers registered at KP2KP Sungguminasa. A quantitative associative causal method was applied, using primary data collected through questionnaires distributed to 100 respondents selected by purposive sampling from a population of 180,000 registered taxpayers. Data were analyzed using multiple linear regression with SPSS version 27.The results indicate that local government transparency has a positive and significant effect on individual taxpayer compliance, with a regression coefficient of 0.377 and a significance value of 0.001. Public trust also has a positive and significant influence, with a regression coefficient of 0.510 and a significance value of 0.001. Simultaneously, both variables significantly affect taxpayer compliance, as shown by an F-value of 77.555 and a significance level of 0.000. The coefficient of determination (R²) of 0.615 reveals that 61.5% of the variation in taxpayer compliance is explained by transparency and public trust, while 38.5% is influenced by other factors outside the model.